Examining the Influence of Corporate Reputation and Work Environment on Generation Z’s Job Application Intentions: A Literature Review - Sven, Gunther (Lighthouse Publishing, 2025)
The job application intentions of Generation Z are increasingly influenced by corporate reputation and work environment. This literature review synthesizes key studies examining these factors and their impact on job-seeking behavior. The findings highlight that Generation Z values intangible workplace attributes such as culture, ethics, and employer branding alongside job characteristics. Digital recruitment platforms and online employer reviews significantly shape perceptions, with trust and information credibility playing crucial roles. Moreover, corporate social responsibility (CSR) and strategic employer branding enhance organizational attractiveness. This study underscores the importance of a strong employer reputation and a positive work environment in attracting young talent.